A aplicação da matemática financeira no empreendedorismo: uma ferramenta de competitividade no mundo globalizado - SOUSA NETO, José De Ribamar (2022)
This master's thesis addresses the application of financial mathematics in entrepreneurship as a competitiveness tool in the globalized world. Thus, it presents financial mathematics in the competitive business world. The general objective of this research was to discuss the importance of the applicability of financial mathematics as strategic and competitive support in the world of entrepreneurship. While the specific objectives are to discuss specific milestones regarding Entrepreneurship; ratify the importance of Entrepreneurial Education today; address concepts of Financial Mathematics and their applicability in the business world. The methodology made use of qualitative and bibliographic research, in which data collected in journal articles, books and databases were analyzed. The results obtained show us that the entrepreneur has knowledge of financial mathematics for decision making and that there is an academic interest in the topic. Furthermore, investment in basic education is necessary, highlighting entrepreneurial citizen training with a focus on financial mathematics.